Predictors of modern contraceptive use during the postpartum period among women in Uganda: a population-based cross sectional study - Rutaremwa, Gideon; Kabagenyi, Allen; Ojiambo Wandera, Stephen; Jhamba, Tapiwa; Akiror, Edith; Nviiri, Hellen Laetitia (BMC public health, 2015)
The rationale for promotion of family planning (FP) to delay conception after a recent birth is a best practice that can lead to optimal maternal and child health outcomes. Uptake of postpartum family planning (PPFP) remains low in sub-Saharan Africa. However, little is known about how pregnant women arrive at their decisions to adopt PPFP. Methods: We used 3298 women of reproductive ages 15–49 from the 2011 UDHS dataset, who had a birth in the 5 years preceding the survey. We then applied both descriptive analyses comprising Pearson’s chi-square test and later a binary logistic regression model to analyze the relative contribution of the various predictors of uptake of modern contraceptives during the postpartum period. Results: More than a quarter (28%) of the women used modern family planning during the postpartum period in Uganda. PPFP was significantly associated with primary or higher education (OR=1.96; 95% CI=1.43-2.68; OR=2.73; 95% CI=1.88-3.97 respectively); richest wealth status (OR=2.64; 95% CI=1.81-3.86); protestant religion (OR=1.27; 95% CI=1.05-1.54) and age of woman (OR=0.97, 95% CI=0.95-0.99). In addition, PPFP was associated with number of surviving children (OR=1.09; 95 % CI=1.03-1.16); exposure to media (OR=1.30; 95% CI=1.05-1.61); skilled birth attendance (OR=1.39; 95% CI=1.12-1.17); and 1–2 days timing of post-delivery care (OR=1.68; 95% CI=1.14-2.47). Conclusions: Increasing reproductive health education and information among postpartum women especially those who are disadvantaged, those with no education and the poor would significantly improve PPFP in Uganda.
Keywords: Predictors; Postpartum; Family Planning; Contraception; Women; Uganda